Modulation of spin–valley splitting in a two-dimensional MnPSe3/CrBr3 van der Waals heterostructure. (9th January 2020) - Wu, Xuefeng; Zhou, Jiangpeng; Li, Penggang; Wu, Yaping; Wu, Zhiming; Li, Xu; Kang, Junyong
Abstract: We perform a systematic investigation of MnPSe3 /CrBr3 two-dimensional (2D) van der Waals heterostructures through first-principles calculations. The most stable stacking configuration of MnPSe3 /CrBr3 heterostructures is found to have an indirect type-II band structure. Biaxial tensile strain is employed to tailor the spin–valley properties of the heterostructures in terms of the momentum, energy and spin components of the valleys. A novel opposite spin splitting evolution appears at the K and K′ valleys of the top valance band (TVB) with increasing tensile strain. A change from an indirect to a direct band gap is found at 7% tensile strain. A maximum spin splitting of 34.7 meV at the K′ valley is produced simultaneously with valley polarization under a tensile strain of 10%. The spin components distributed at the TVB are found to be controlled by strain-related competition between direct exchange interaction and indirect superexchange interaction of Se (p x + p y ) and Se p z orbitals. Spin polarization precisely regulated by strain can facilitate the manipulation of valley and spin degrees of freedom in MnPSe3 /CrBr3 heterostructures, which opens up great potential for novel applications, such as strained sensor, spintronic and valleytronic devices.